Leadership Styles and Employee Performance: A Systematic Literature Review of Empirical Studies (2020-2025) - Dewi Zulvia; Yunia Wardi; Rino Rino (Owner : Riset dan Jurnal Akuntansi, 2026)
This systematic literature review comprehensively analyzes the relationship between leadership styles and employee performance based on empirical evidence from 2020-2025. The research population comprises employees and leaders across various organizational sectors including education, healthcare, and industry. Using the PRISMA framework with purposive sampling technique, the selection process from an initial pool of 500 studies identified through database searches yielded 14 high-quality empirical studies as the final sample that met the inclusion criteria. The methodology employed systematic literature review with rigorous quality assessment and analysis. Key findings reveal that the relationship between leadership styles and employee performance is predominantly positive and significant, with three distinct patterns emerging. The majority of studies (8 studies) demonstrated dominant positive influence from transformational and servant leadership, while several studies (3 studies) showed positive but non-dominant influence where organizational factors outweighed leadership effects. Notably, no studies found significant negative impacts from constructive leadership styles. Furthermore, the relationship was frequently mediated by variables including ethical organizational culture, knowledge sharing, and job security. In conclusion, this systematic review substantiates that adaptive, empowerment-focused leadership serves as a crucial driver of employee performance, offering substantial practical value for organizations to develop evidence-based, contextual leadership strategies that foster work environments conducive to sustained productivity and organizational excellence in the modern business landscape.